2021
DOI: 10.1186/s12889-021-10972-w
|View full text |Cite
|
Sign up to set email alerts
|

The role of gender power relations on women’s health outcomes: evidence from a maternal health coverage survey in Simiyu region, Tanzania

Abstract: Background Gender is a crucial consideration of human rights that impacts many priority maternal health outcomes. However, gender is often only reported in relation to sex-disaggregated data in health coverage surveys. Few coverage surveys to date have integrated a more expansive set of gender-related questions and indicators, especially in low- to middle-income countries that have high levels of reported gender inequality. Using various gender-sensitive indicators, we investigated the role of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 49 publications
2
15
0
Order By: Relevance
“…The study employed the gender roles framework developed by the Harvard Institute for International Development in the selection and classification of women empowerment variables [ 10 , 11 , 17 ]. The framework categorizes women’s empowerment variables into;influencing, resource and decision-making factors.…”
Section: Methodsmentioning
confidence: 99%
“…The study employed the gender roles framework developed by the Harvard Institute for International Development in the selection and classification of women empowerment variables [ 10 , 11 , 17 ]. The framework categorizes women’s empowerment variables into;influencing, resource and decision-making factors.…”
Section: Methodsmentioning
confidence: 99%
“…We structured the final search strategy around three elements, with each required to appear in titles or abstracts of selected studies 1 : gender discrimination-related terms, 2 health terms and 3 LMICs context-related terms. This strategy is represented in table 2 .…”
Section: Methods and Analysismentioning
confidence: 99%
“…It is also recognised that GBD affects women’s health more broadly, by shaping resource allocation, both within and outside the household, and limiting access to health services. 3 4 In addition, besides the well-known correlation between age, poverty, education and access to medical facilities, emerging evidence suggests that the experience of GBD may contribute to the high levels of maternal mortality still observed in many regions of the world. 5 6 Thus, reducing GBD against women is postulated as an essential step towards achieving Target 3.1 of the SDGs, which demands a strong decrease in maternal mortality by 2030.…”
Section: Introductionmentioning
confidence: 99%
“…The literature also acknowledged the potential discrepancy in responses between women and men and among both on transforming power relations due to their social acceptability bias (Garrison-Desany et al, 2021). A study of gender training in NGOs that work at the grassroots examined its effectiveness in altering the equations of power, both within and in institutions, enabling women staff to discover the power within themselves and raising awareness among male staff (Murthy, 1998).…”
Section: Concept Of Powermentioning
confidence: 99%
“…EIGE's (2016) in-depth study on gender training in the EU found that improved individual gender competence leads to positive gender mainstreaming. In the case of ASHAs (grass-roots level health workers in India), training enabled them to envision taking a more active role and increased their confidence (Garrison-Desany et al, 2021). Teachers who participated in training to promote Gender Equality in schools were less sexist and promoted autonomy to a greater extent (Kollmayer et al, 2020).…”
Section: Behaviour -Knowledge Transfermentioning
confidence: 99%